2021
DOI: 10.1002/solr.202100464
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Molecule Engineered SnO2 for Perovskite Solar Cells with High Efficiency and Reduced Lead Leakage

Abstract: Owing to the low exciton dissociation energy, long charge carrier lifetime, high absorption coefficient, and the ease of large-area fabrication of hybrid perovskite thin films, perovskite solar cells (PSCs) have attracted extensive attention during the past decade. [1][2][3][4][5][6][7][8][9][10][11] To date, the power conversion efficiency (PCE) of the stateof-the-art perovskite solar devices has been boosted from 3.8% [12] to a certified 25.5%. [13] Except for the composition (the types of cations and anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 53 publications
0
36
0
2
Order By: Relevance
“…A relatively stable PCE of 25.0% at MPP was observed after 1200 s, which corresponds to one of the highest efficiencies reported for an n-i-p-type perovskite/silicon tandem device based on spiro-OMeTAD as HTL. [40,41] We also investigated the impact of the 3:3 and 3:5 dopant ratios on device stability. Figure 4e shows the stabilities of unencapsulated devices under continuous irradiation with light and in air (at 25 °C with a humidity of about 20%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively stable PCE of 25.0% at MPP was observed after 1200 s, which corresponds to one of the highest efficiencies reported for an n-i-p-type perovskite/silicon tandem device based on spiro-OMeTAD as HTL. [40,41] We also investigated the impact of the 3:3 and 3:5 dopant ratios on device stability. Figure 4e shows the stabilities of unencapsulated devices under continuous irradiation with light and in air (at 25 °C with a humidity of about 20%).…”
Section: Resultsmentioning
confidence: 99%
“…A relatively stable PCE of 25.0% at MPP was observed after 1200 s, which corresponds to one of the highest efficiencies reported for an n–i–p ‐ type perovskite/silicon tandem device based on spiro‐OMeTAD as HTL. [ 40,41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Na 3 PO 4 can effectively passivate the buried interface of perovskite film, leading to more uniform and homogeneous crystals with less residual PbI 2 and large crystal size in the final films. [ 31,32 ] It has also been reported that a moderate amount of excessive PbI 2 will passivate the grain boundaries, [ 33 ] while large amount of PbI 2 would greatly reduce the stability of the device. [ 34 ] Here in the case of SnO 2 :Na 3 PO 4 ‐based perovskite film has small amount of PbI 2 , which is better for grain boundary passivation than the pristine SnO 2 ‐based perovskite film with large amount of PbI 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 106 ] Copyright 2021, Wiley‐VCH. f) The schematic of mechanisms of the perovskite growth on SnO 2 and ATMP optimized SnO 2 .…”
Section: Strategies For Minimizing Pb Leakagementioning
confidence: 99%
“…Reproduced with permission. [ 106 ] Copyright 2021, Wiley‐VCH. h) Schematic diagram of Pb detection on the surface of ETLs after different washing times.…”
Section: Strategies For Minimizing Pb Leakagementioning
confidence: 99%